2014
DOI: 10.1111/sji.12245
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin‐2 Promotes M1 Macrophages Polarization in a Mouse Cardiac Ischaemia–Reperfusion Injury Model

Abstract: Ischaemia-reperfusion (IR) injury is a major issue in cardiac transplantation. Inflammatory processes play a major role in myocardial IR injury. Lipocalin-2 (Lcn2), which is also known as neutrophil gelatinase-associated lipocalin, has multiple functions that include the regulation of cell death/survival, cell migration/invasion, cell differentiation and iron delivery. In our study, the hearts of C57BL/6 mice were flushed with and stored in cold Bretschneider solution for 8 h and then transplanted into a synge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 36 publications
0
34
0
Order By: Relevance
“…and MCP-1 (5). Finally, it has been shown that NGAL was involved in the polarization of macrophages towards the pro-inflammatory phenotype M1, in vitro and in vivo (89,109).…”
Section: Ngal and Pro-inflammatory Cytokines Expressionmentioning
confidence: 96%
See 1 more Smart Citation
“…and MCP-1 (5). Finally, it has been shown that NGAL was involved in the polarization of macrophages towards the pro-inflammatory phenotype M1, in vitro and in vivo (89,109).…”
Section: Ngal and Pro-inflammatory Cytokines Expressionmentioning
confidence: 96%
“…In addition, increasing NGAL circulating levels of NGAL KO mice using an NGAL encoding adenovirus treatment resulted in impaired cardiac functional recovery and decreased mitochondrial function of the isolated-perfused hearts (90). In a mouse model of I/R after heart transplantation, the use of anti-NGAL antibodies reduced the infiltration of macrophages and neutrophils into the ischemic zone, suppressed the M1 polarization of macrophages, and blunted the I/R-induced cardiac lesions (89).…”
Section: Ngal In Cardiovascular Ischemiamentioning
confidence: 99%
“…A recent study revealed lipocalin2 (Lcn2), a defense mediator expressed in response to TLR activation, plays a crucial role in cardiac IRI, and neutralization of Lcn2 suppressed M1 macrophage polarization and instead mediated skewing of macrophages toward an M2 phenotype. Additionally, Lcn2 treatment suppressed infiltration of macrophages further limiting IRI [36]. …”
Section: Macrophages In Ischemia Reperfusion Injurymentioning
confidence: 99%
“…The expression of Lcn-2 is markedly upregulated in injured spinal cord and brain tissue (13,14). The involvement of Lcn-2 in the systemic response to IR has been documented in previous studies of the heart and kidneys (15)(16)(17).…”
Section: Introductionmentioning
confidence: 80%
“…It is speculated that oxidative radical-induced inflammation is crucially involved during the progression of CIR injury (17). Since miRs were identified as common regulators of DNA transcription and mRNA translation, numerous miRs have been associated with oxidative radical-mediated pathophysiological alterations (19).…”
Section: Discussionmentioning
confidence: 99%